Structural, Physicochemical, and Functional Properties of Electrolyzed Cassava Starch - Khanh Son Trinh; Thanh Binh Dang (International Journal of Food Science)
Cassava starch was oxidized using the electrolysis system. Sodium chloride was added to this system at various concentrations from 0.5 to 5.0 % (w/v). The whiteness of modified starches proportionally increased based on the NaCl concentration and human eyes could recognize the difference of color. Under treatment, dents occurred on the surface of starch granule. Concentration of carbonyl and carboxyl groups was increased compared to native starch. Based on X-ray diffraction pattern, oxidized starch kept its A-type. Besides, the ratios of alpha-helix/amorphous regions remained indicating oxidation reaction mainly subjected on amorphous region. Intrinsic viscosity was used to indirectly calculate the average molecular weight of sample. Furthermore, results showed that average molecular weight was significantly reduced (from 2.09-fold to 13.22-fold) based on the reacting NaCl concentration. The increase of NaCl content related to the increase of retrogradation of treated starches. At various temperatures (30-95°C), swelling factor and clarity reflected negative and positive correlations to NaCl concentration.